2007
DOI: 10.3844/jssp.2007.185.189
|View full text |Cite
|
Sign up to set email alerts
|

Auditors Compliance with International Standards on Auditing (ISAs): Evidence form Jordan

Abstract: Abstract:The continuous new amendments of the International Standards on Auditing (ISAs) in the beginning of 2007 formed a pressure on auditors to follow up and comply with them. The present study attempted to examine to what extent auditors complied with ISA according to the last pronouncement by the International Auditing and Assurance Standard Board (IAASB). Data was collected through a questionnaire administered to a random sample of external auditors in Jordan. The study revealed that Jordanian auditors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The finding of this study consistent with Obaidat (2007) who found that Jordanian external auditors comply with the ISAs and aware of their importance on audit quality. Although Obaidat"s study showed that ISA 260 gained a low rank of compliance, in comparison with the other standards, this however, could be explained to the fact that his study was conducted before the establishment of the first version of the Jordanian corporate governance code for public shareholding companies in 2009, which has vested the audit committee a significant role in facilitating the work of the external auditors and organized the mechanism of the communication between auditors and the company.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding of this study consistent with Obaidat (2007) who found that Jordanian external auditors comply with the ISAs and aware of their importance on audit quality. Although Obaidat"s study showed that ISA 260 gained a low rank of compliance, in comparison with the other standards, this however, could be explained to the fact that his study was conducted before the establishment of the first version of the Jordanian corporate governance code for public shareholding companies in 2009, which has vested the audit committee a significant role in facilitating the work of the external auditors and organized the mechanism of the communication between auditors and the company.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Jordan was an early reformer in terms of adopting accounting standards, auditing standards, and corporate governance initiatives in the region (Obaidat, 2007;Shehata, 2015;Al-Frijat, 2016). Obaidat (2007) investigated Jordanian auditors" compliance with the ISAs. A questionnaire was designed by listing all auditing standards and sought auditors" views about the extent of their compliance with the standards.…”
Section: Introductionmentioning
confidence: 99%